Biopsychological correlates of repetitive and restricted behaviors in autism spectrum disorders - Miguel Comparan‐Meza; Ivette Vargas de la Cruz; Fernando Jauregui‐Huerta; Rocio E. Gonzalez‐Castañeda; Oscar Gonzalez‐Perez; Alma Y. Galvez‐Contreras (Brain and Behavior, 2021)
Abstract Background Autism Spectrum Disorder (ASD) is considered a neurodevelopmental condition that is characterized by alterations in social interaction and communication, as well as patterns of restrictive and repetitive behaviors (RRBs). RRBs are defined as broad behaviors that comprise stereotypies, insistence on sameness, and attachment to objects or routines. RRBs can be divided into lower‐level behaviors (motor, sensory, and object‐manipulation behaviors) and higher‐level behaviors (restrictive interests, insistence on sameness, and repetitive language). According to the DSM‐5, the grade of severity in ASD partially depends on the frequency of RRBs and their consequences for disrupting the life of patients, affecting their adaptive skills, and increasing the need for parental support. Methods We conducted a systematic review to examine the biopsychological correlates of the symptomatic domains of RRBs according to the type of RRBs (lower‐ or higher‐level). We searched for articles from the National Library of Medicine (PubMed) using the terms: autism spectrum disorders, ASD, and autism‐related to executive functions, inhibitory control, inflexibility, cognitive flexibility, hyper or hypo connectivity, and behavioral approaches. For describing the pathophysiological mechanism of ASD, we also included animal models and followed PRISMA guidelines. Results One hundred and thirty‐one articles were analyzed to explain the etiology, continuance, and clinical evolution of these behaviors observed in ASD patients throughout life. Conclusions Biopsychological correlates involved in the origin of RRBs include alterations in a) neurotransmission system, b) brain volume, c) inadequate levels of growth factors, d) hypo‐ or hyper‐neural connectivity, e) impairments in behavioral inhibition, cognitive flexibility, and monitoring and f) non‐stimulating environments. Understanding these lower‐ and higher‐level of RRBs can help professionals to improve or design novel therapeutic strategies.